Bleeding events and safety outcomes in persons with haemophilia A with inhibitors: A prospective, multi‐centre, non‐interventional study. Issue 6 (8th October 2018) - Mahlangu, Johnny; Oldenburg, Johannes; Callaghan, Michael U.; Shima, Midori; Santagostino, Elena; Moore, Maggie; Recht, Michael; Garcia, Claudia; Yang, Renchi; Lehle, Michaela; Macharia, Harrison; Asikanius, Elina; et al.
Abstract: Introduction: Prospectively collected, real‐world data on bleeds, haemophilic treatment and safety outcomes in persons with haemophilia A (PwHA) with factor VIII (FVIII) inhibitors are limited. A prospective, global, multi‐centre, non‐interventional study (NIS; NCT02476942) collected detailed real‐world data in PwHA treated per local routine clinical practice. Aim: To characterize bleeding rates, haemophilic treatment practices, prophylaxis adherence and adverse events (AEs) in adult/adolescent PwHA with inhibitors in the NIS. Methods: Participants aged ≥12 years with congenital haemophilia A/documented high‐titre FVIII inhibitor history were enrolled. Participants remained on their usual treatment; no interventions were applied. Results: Overall, 103 PwHA with inhibitors enrolled, (median [range] age 31 [12‐75] years) and were monitored for median (range) 26.0 (4.1‐69.6) weeks. In the episodic (n = 75) and prophylactic (n = 28) treatment groups, respectively, 1244 and 325 bleeds were reported, and 528 (42.4%) and 104 (32.0%) were not treated; annualized bleeding rates (ABRs; 95% confidence interval) were 18.6 (15.2‐22.8) and 14.9 (10.5‐21.2) for treated bleeds, and 32.7 (27.3‐39.1) and 25.0 (18.4‐34.0) for all bleeds. Coagulation products used included activated prothrombin complex concentrate (aPCC) and/or recombinant activated FVII. Among participants prescribed aPCC prophylaxis, 35.0% adhered to both prescribed frequency of aPCC administration and prescribed dose. Serious AEs of haemarthrosis and muscle haemorrhage were reported; most common AEs were arthralgia, viral upper respiratory tract infection and pyrexia. Conclusions: ABRs (treated bleeds and all bleeds) remain high on standard treatment; this prospective NIS demonstrates the need for more effective treatments for PwHA with inhibitors to reduce/prevent bleeds, with potential to improve prophylaxis adherence and further improve outcomes.